Patterns of multiple sclerosis presentation to the emergency department - Makkawi, Seraj; Maglan, Alaa; Khojah, Osama; Allaf, Faris; Alamoudi, Saeed; Ahmed, Mohamed Eldigire; Alsharif, Rawaf; Altayeb, Meral; Alharthi, Abdulrhman; Abulaban, Ahmad; Al Malik, Yaser (Frontiers in Neurology, 2024)
Background: Multiple sclerosis (MS) patients are no strangers to the emergency department (ED) due to the relapsing and progressive nature of the disease and the associated complications. This study aimed to identify patterns of ED visits among patients diagnosed with MS, the underlying causes of these visits, and the factors associated with these visits. Methods: This was a single center retrospective cohort study which utilized a non-probability consecutive sampling technique to include all patients diagnosed with MS (471 patients) from March 2016 to October 2021 in King Abdulaziz Medical City, Jeddah, Saudi Arabia. ED visits were categorized as directly related to MS, indirectly related to MS, or unrelated to MS. Results: One in four people with MS visited the ED at least once with a total of 280 ED visits. Most ED visits were ones directly related to MS 43.6%, closely followed by unrelated to MS 41.1%, and then indirectly-related MS visits 15.4%. The most common presenting symptoms in directly-related MS visits were weakness 56.6% and numbness/tingling 56.6% followed by gait impairment 29.5%. Indirectly related to MS or unrelated to MS ED visits were commonly due to neurological 17.7% and gastrointestinal 17.1% causes. Using disease modifying therapy (DMT) was significantly associated with no ED visits (p<0.001). The use of high-efficacy DMTs was significantly associated with no ED visits than using moderate efficacy DMT (p<0.001). The use of B-cell depleting therapy (ocrelizumab and rituximab) was significantly associated with no visits to the ED than using any other DMT (p<0.001). Evidence of brain atrophy on imaging was significantly associated with patients who presented to the ED ≥3 times (p=0.006, UOR=3.92). Conclusion: Due to the nature of the disease, many MS patients find themselves visiting the ED due to MS related and unrelated issues. These patients are not only required to be treated by neurologists but also by multiple disciplines. The use of high-efficacy DMTs and B-cell depleting therapy may reduce the total frequency of ED visits. Special attention should be paid to patients who have evidence of brain atrophy on imaging.